Sustained Virologic Response with Direct Acting Antivirals in HIV Coinfected Hepatitis C Patients and Its Effect on Liver Fibrosis. (4th October 2017) - Lebron, Dora; Stang, Alexandra; Lagasca, Alicia; Cook, Paul P; Siraj, Dawd
Abstract: Background: Hepatitis C virus (HCV) is an important cause of chronic hepatitis resulting in end stage liver disease and hepatocellular carcinoma. Direct acting antivirals (DAAs) interfere with the HCV lifecycle and result in high rates of sustained virologic response (SVR). We hypothesized that treatment with DAAs in a real world setting is as successful in HCV/HIV coinfected patients as it is in HCV monoinfected patients, and that some degree of fibrosis regression can be observed after completion of therapy in both groups. Methods: We retrospectively reviewed data from patients who received treatment for HCV from 2014 to 2016 at the Infectious Diseases clinic and collected demographic characteristics, HCV genotype and viral load, DAA regimen, SVR rates, and whether or not fibrosis improved at 12 or 24 weeks after treatment completion defined as one METAVIR stage improvement in FibroSURE™ score to estimate fibrosis. In those with HIV, HIV viral load, CD4 count and HIV antiretroviral regimen were examined. Results: Out of 41 patients in each group, 24 had completed therapy in the monoinfected group and 26 in the coinfected group. In the monoinfected group, 22 (92%) achieved SVR. In the coinfected group, 26 (100%) achieved SVR. The SVR rates of the monoinfected group and coinfected group did not differ significantly ( P = .956). In the monoinfected group, 10/17 (59%) had an improvement in FibroSURE™ score, and 7/17 (41%) had no change. In the coinfected group, 2/9 (22.2%) patients demonstrated an improvement in FibroSURE™ score, 4/9 (44.4%) had no change, and 3/9 (33%) had an increase in FibroSURE™ score. There was no significant difference in the change in FibroSURE™ score before and after SVR between the two groups ( P =  .100). Conclusion: In this small study, although not statistically significant, coinfected patients treated with DAAs had higher SVR rates than monoinfected patients. Treatment failure in the monoinfected group was linked to nonadherence, whereas, success of the coinfected patients was likely related to engagement in routine HIV care. Although not statistically significant, there were more patients in the monoinfected group that had an improvement in FibroSURE™ score, however the small sample size precludes any definitive conclusions. Disclosures: P. P. Cook, Merck: Speaker's Bureau, Grant recipient; Pfizer: Shareholder, Grant recipient; Gilead: Clinical Trials, Grant recipient; D. Siraj, Gilead: Speaker's Bureau, Grant recipient